Conductive glass fiber cloth
By applying mixed ink of low-melting point glass powder and conductive components on the glass fiber cloth and calcining it to form a carbonized conductive layer, the problems of long production cycle, high cost and inapplicable to thin glass fiber cloth in the prior art are solved, and the high performance and wide applicability of the conductive glass fiber cloth are achieved.
Patent Information
- Application Number
- CN202411723986.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
In the prior art, when preparing conductive glass fiber cloth, the chemical vapor deposition method has problems such as long preparation cycle, high process cost and high energy consumption, and is not suitable for thin glass fiber cloth.
A low-melting glass powder is used as a functional filler, and a carbonized conductive layer is obtained by coating conductive ink and calcining under an inert atmosphere, and a conductive layer on a glass fiber base cloth is formed.
It realizes uniform square resistance, high stability, good coating fastness, excellent impact resistance, and suitable for thin glass fiber cloth.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functionalized preparation of glass fiber cloth, and particularly relates to a conductive glass fiber cloth. Background Art
[0002] The conductive glass fiber cloth obtained by depositing a layer of graphene film on the surface of the glass fiber cloth by chemical vapor deposition has excellent electric heating performance and high stability. However, this method has the problems of long preparation cycle, high process cost and high energy consumption, and is only suitable for glass fiber cloth with higher grammage and high temperature resistance. This is because the extremely high growth temperature (960-1100°C) in the chemical vapor deposition method promotes the decomposition of carbon sources such as methane and the growth of graphene crystals, while also significantly reducing the strength of the glass fiber bundle, making it easy to break and pulverize when torn by external force. This phenomenon is more serious when using thin glass fiber cloth or a longer growth time. Summary of the Invention
[0003] In response to the problems existing in the above-mentioned technology, the purpose of the present invention is to provide a conductive glass fiber cloth with uniform and stable square resistance, good coating adhesion, excellent impact resistance, and suitable for the conductive functionalization of thin glass fiber cloth.
[0004] In order to achieve the purpose, the present invention adopts the following technical solutions:
[0005] The present invention provides a conductive glass fiber cloth, which comprises a glass fiber base cloth and a carbonized conductive layer formed on the glass fiber base cloth.
[0006] The carbonized conductive layer is obtained by coating and calcining a conductive ink. The conductive ink comprises the following components by weight: 10-30 parts of low-melting-point glass powder, 3-5 parts of graphene, 0.5-2 parts of single-walled carbon nanotubes, 0.1-0.5 parts of conductive carbon black, 5-10 parts of resin, 0.1-0.3 parts of dispersant, 0.01-0.03 parts of anti-settling thixotropic agent, 0.01-0.05 parts of silane coupling agent, 70-90 parts of water, and 5-20 parts of ethanol.
[0007] Preferably, the low-melting-point glass powder has a specification of 1500 mesh to 3000 mesh.
[0008] Preferably, the graphene sheet diameter is ≤6 μm, and the number of layers is 6-10.
[0009] Preferably, the single-walled carbon nanotube has a diameter of 1-2 nm and a length of 10-30 μm.
[0010] Preferably, the conductive carbon black has a mesh size of 1000-2000 mesh.
[0011] Preferably, the resin is at least one of polyurethane resin and ceramic resin.
[0012] Preferably, the dispersant is polyvinyl pyrrolidone K30.
[0013] Preferably, the anti-settling thixotropic agent is a polyamide wax or a polyethylene wax.
[0014] Preferably, the silane coupling agent is one of vinyl silane, amino silane and methacryloxy silane.
[0015] Furthermore, the method for preparing the conductive glass fiber cloth of the present invention comprises the following steps:
[0016] S1. Cleaning and drying the glass fiber cloth to obtain a clean glass fiber cloth;
[0017] S2. Evenly mix 10-30 parts of low-melting-point glass powder, 3-5 parts of graphene, 0.5-2 parts of single-walled carbon nanotubes, 0.1-0.5 parts of conductive carbon black, 5-10 parts of resin, 0.1-0.3 parts of dispersant, 0.01-0.03 parts of anti-settling thixotropic agent, and 0.01-0.05 parts of silane coupling agent in a mixed solvent of 70-90 parts of water and 5-20 parts of ethanol to obtain a conductive ink; apply the conductive ink on a clean glass fiber cloth, and dry it to obtain a glass fiber cloth coated with a conductive layer;
[0018] S3. calcining the glass fiber cloth coated with the conductive layer under an inert atmosphere, and cooling the glass fiber cloth to obtain a conductive glass fiber cloth.
[0019] Furthermore, the conductive ink is coated on the glass fiber cloth by spraying or dipping, and the dipping coating and post-treatment are repeated several times to achieve the target square resistance. The dry weight of the conductive ink is 2 to 30 g / m 2 .
[0020] Furthermore, the inert atmosphere is one of nitrogen, helium and argon.
[0021] Furthermore, the calcination adopts a gradient temperature rising calcination method, the steps of which are: first heating to the drainage temperature of 130-150°C, keeping warm for 5-10 minutes; then heating to the carbon discharge temperature of 350-380°C, keeping warm for 5-10 minutes; and continuing to heat to the sintering temperature of 400-600°C, keeping warm and calcining for 10-30 minutes.
[0022] Compared with the prior art, the beneficial effects of the present invention are embodied in:
[0023] 1. This invention uses low-melting-point glass flakes as a functional filler added to the conductive layer, improving the coating's toughness, wear resistance, and durability. An anti-settling thixotropic agent effectively improves the dispersibility and stability of the glass flakes in the coating, reducing sedimentation. A silane coupling agent enhances the compatibility of the low-melting-point glass flakes with the resin, resulting in excellent adsorption properties, easy mixing, and no agglomeration.
[0024] 2. The present invention performs a calcination treatment on the conductive layer under the protection of an inert gas. The organic components in the conductive layer are calcined at a certain temperature to be carbonized. Due to the escape of volatile components and the change of molecular structure, especially the increase in the size of graphite crystallites, the sheet resistance of the coating can be significantly reduced, and the conductivity of the electron transmission network composed of graphene, carbon nanotubes and carbon black can be further increased.
[0025] 3. This invention utilizes a relatively low temperature to calcine and carbonize the conductive layer, avoiding the damage to the glass fiber cloth caused by high-temperature CVD (960-1100°C) treatment. Furthermore, when the temperature reaches the sintering temperature, the low-melting-point glass powder begins to melt, forming a bond with the glass fiber cloth and forming a protective layer, ensuring the structural stability of the conductive network on the glass fiber cloth.
[0026] 4. After calcination and cooling, the low-melting-point glass powder of the present invention forms an inorganic glass-like heat-conducting layer, which can quickly conduct away the heat of the packaging part, help control the temperature, and improve the heating uniformity of the conductive glass fiber cloth. DETAILED DESCRIPTION
[0027] The present invention is described in detail below in conjunction with the embodiments. The following embodiments are implemented on the premise of the technical solution of the present invention, and provide detailed implementation methods and specific operating processes, but the protection scope of the present invention is not limited to the following embodiments.
[0028] The low-melting-point glass powder used in the following examples has a specification of 2000 mesh, an average particle size of 8 μm, and an initial melting temperature of 445° C., and is provided by Anmi Micro-Nano New Materials (Guangzhou) Co., Ltd.
[0029] The graphene sheets used in the following examples have a diameter of ≤6 μm, a number of 6-10 layers, model WJ-GP550, and are produced by Hefei Microcrystalline Material Technology Co., Ltd.
[0030] The single-walled carbon nanotubes used in the following examples have a diameter of 1-2 nm, a length of 10-30 μm, and are model XFS16-1, and are provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0031] The conductive carbon black used in the following examples has a mesh size of 2000 mesh, model XC-72, and is provided by Shanghai Jingyan Chemical Co., Ltd.
[0032] The modified waterborne polyurethane emulsion used in the following examples was purchased from Yierfu Chemical (Shanghai) Co., Ltd., model PU-6155, with a solid content of 40%.
[0033] The ceramic resin used in the following examples was provided by Zongyang Sanjin Pigment Co., Ltd., model SJ-592, with a solid content of 35%.
[0034] The polyvinyl pyrrolidone, anti-settling thixotropic agent and silane coupling agent used in the following examples were all purchased from Sinopharm Chemical Reagent Co., Ltd.
[0035] Example 1
[0036] This embodiment provides a conductive glass fiber cloth, comprising a glass fiber base cloth and a carbonized conductive layer formed on the glass fiber base cloth, wherein the preparation method thereof comprises the following steps:
[0037] S1, glass fiber cloth (weight per unit area 48g / m 2 , thickness of 0.03 mm) were washed with acetone and deionized water in sequence and then dried to obtain a clean glass fiber cloth.
[0038] S2. 20 parts of low-melting-point glass powder, a graphene dispersion containing 3 parts of graphene, a carbon nanotube dispersion containing 2 parts of single-walled carbon nanotubes, 0.3 parts of conductive carbon black, a modified polyurethane emulsion containing 5 parts of polyurethane resin, 0.3 parts of polyvinyl pyrrolidone, 0.02 parts of polyamide wax, and 0.02 parts of vinyl silane are uniformly mixed in a mixed solvent of 90 parts of water and 10 parts of ethanol to obtain a conductive ink; the conductive ink is dip-coated on a clean glass fiber cloth, and then a post-treatment process including extrusion, drying, and cooling is carried out in sequence, and the dip-coating and post-treatment steps are repeated twice to obtain a glass fiber cloth coated with a conductive layer. The dry weight of the conductive layer coating is 6.0 g / m 2 .
[0039] S3. The glass fiber cloth coated with the conductive layer is calcined under a nitrogen atmosphere by first heating to 150°C (water removal temperature) and holding the temperature for 5 minutes; then heating to 350°C (carbon removal temperature) and holding the temperature for 5 minutes; then heating to 450°C (sintering temperature) and holding the temperature for 30 minutes. The conductive glass fiber cloth is then cooled to obtain.
[0040] Example 2
[0041] This embodiment provides a conductive glass fiber cloth, comprising a glass fiber base cloth and a carbonized conductive layer formed on the glass fiber base cloth, wherein the preparation method thereof comprises the following steps:
[0042] S1, glass fiber cloth (weight per unit area 25g / m 2, thickness of 0.02 mm) were washed with acetone and deionized water in sequence and then dried to obtain a clean glass fiber cloth.
[0043] S2. 10 parts of low-melting-point glass powder, a graphene dispersion containing 5 parts of graphene, a carbon nanotube dispersion containing 0.5 parts of single-walled carbon nanotubes, 0.5 parts of conductive carbon black, a ceramic resin liquid containing 10 parts of ceramic resin, 0.2 parts of polyvinyl pyrrolidone, 0.01 parts of polyethylene wax, and 0.01 parts of methacryloxysilane are mixed uniformly in a mixed solvent of 70 parts of water and 20 parts of ethanol to obtain a conductive ink; the conductive ink is dip-coated on a clean glass fiber cloth, and then a post-treatment process including extrusion, drying, and cooling is carried out in sequence, and the dip-coating and post-treatment steps are repeated once to obtain a glass fiber cloth coated with a conductive layer. The dry weight of the conductive layer coating is 4.8 g / m 2 .
[0044] S3. Calcine the conductive-layered glass fiber cloth under a nitrogen atmosphere by first heating it to 130°C, a water discharge temperature, and holding it for 5 minutes; then heating it to 380°C, a carbon discharge temperature, and holding it for 10 minutes; and then heating it to 480°C, a sintering temperature, and calcining it for 20 minutes. After cooling, the conductive glass fiber cloth is obtained.
[0045] Example 3
[0046] This embodiment provides a conductive glass fiber cloth, comprising a glass fiber base cloth and a carbonized conductive layer formed on the glass fiber base cloth, wherein the preparation method thereof comprises the following steps:
[0047] S1, glass fiber cloth (weight per unit area is 100g / m 2 , thickness of 0.2 mm) were washed with acetone and deionized water in sequence and then dried to obtain a clean glass fiber cloth.
[0048] S2. 30 parts of low-melting-point glass powder, a graphene dispersion containing 4 parts of graphene, a carbon nanotube dispersion containing 1 part of single-walled carbon nanotubes, 0.1 part of conductive carbon black, a modified polyurethane emulsion containing 3 parts of polyurethane resin, a ceramic resin liquid containing 3 parts of ceramic resin, 0.3 parts of polyvinyl pyrrolidone, 0.03 parts of polyamide wax, and 0.05 parts of aminosilane are mixed uniformly in a mixed solvent of 85 parts of water and 5 parts of ethanol to obtain a conductive ink; the conductive ink is applied to a clean glass fiber cloth by single-sided spraying, and then the post-treatment steps of drying and cooling are carried out in sequence, and the spraying and post-treatment are repeated once on the other side to obtain a glass fiber cloth coated with a conductive layer. The dry weight of the conductive layer coating is 26.2 g / m 2 .
[0049] S3. Calcine the conductive-layered glass fiber cloth under a nitrogen atmosphere by first heating it to 150°C, a water discharge temperature, and holding it for 5 minutes; then heating it to 380°C, a carbon discharge temperature, and holding it for 10 minutes; and then heating it to 550°C, a sintering temperature, and calcining it for 30 minutes. After cooling, the conductive glass fiber cloth is obtained.
[0050] Comparative Example 1
[0051] In this comparative example, conductive glass fiber cloth was prepared in the same manner as in Example 1, with the only difference being that no low-melting-point glass powder was added to the conductive ink when preparing the conductive layer.
[0052] Comparative Example 2
[0053] In this comparative example, conductive glass fiber cloth was prepared in the same manner as in Example 1, except that no low-melting-point glass powder was added to the conductive ink when preparing the conductive layer, and the dry weight of the conductive layer was adjusted to 6.0 g / m 2 .
[0054] Comparative Example 3
[0055] In this comparative example, the conductive glass fiber cloth was prepared in the same manner as in Example 1, except that step S3 was not performed during the preparation of the conductive glass fiber cloth.
[0056] Comparative Example 4
[0057] In this comparative example, conductive glass fiber cloth was prepared in the same manner as in Example 1, except that no low-melting-point glass powder was added to the conductive ink during the preparation of the conductive layer, and step S3 was not performed.
[0058] Comparative Example 5
[0059] In this comparative example, conductive glass fiber cloth was prepared in the same manner as in Example 1, except that no low-melting-point glass powder was added to the conductive ink when preparing the conductive layer, and the dry weight of the conductive layer was adjusted to 6.0 g / m 2 , and step S3 is not performed.
[0060] The properties of the conductive glass fiber cloths obtained in the above examples and comparative examples were tested and compared using the following testing methods. The results are shown in Table 1.
[0061] (1) Dry weight of coating: Cut the glass fiber cloth coated with the conductive layer into three square specimens of 100 mm × 100 mm and weigh them on an electronic balance with an accuracy of 0.0001 g. Calculate the arithmetic mean of the dry weight of the coating.
[0062] (2) Adhesion fastness: The glass fiber cloth coated with the conductive layer or the obtained conductive glass fiber cloth was subjected to the 3M tape test method to evaluate the coating adhesion fastness.
[0063] (3) Square resistance and coefficient of variation: The obtained conductive glass fiber cloth was cut into test samples with a length of 250 mm and a width of 200 mm. One side was divided into 20 test areas. The square resistance of each area was tested using a four-probe tester, and the arithmetic mean and coefficient of variation were calculated.
[0064] (4) Heating temperature: Cut the obtained conductive glass fiber cloth into 100 mm × 100 mm square samples, select the opposite edges in the length direction to coat with conductive silver paste, dry and cool, and connect to an AC voltage regulating power supply. At the same time, use an infrared imager to detect the heating temperature of the conductive glass fiber cloth. After power is turned on, slowly increase the output working voltage and adjust it to the heating target temperature of 120 °C.
[0065] (5) Repeated heating resistance change rate: Apply the rated working voltage to the sample to be tested, power on continuously for 16 hours, then turn off the power and cool for 8 hours. After repeatedly powering on and off 25 times, use a multimeter to measure the resistance at both ends of the electrode and calculate the resistance change rate.
[0066] (6) Tensile strength / elastic modulus: The conductive glass fiber cloth was cut into three pieces of specimens with a length of 250 mm and a width of 25 mm. The specimens were placed in a tensile testing machine at a tensile speed of 50 mm / min and the arithmetic mean was calculated.
[0067] The test results of the above examples and comparative examples are shown in Table 1.
[0068] Table 1
[0069] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 <![CDATA[Coating dry weight (g / m 2 )]]> 6.0 4.8 26.2 4.0 6.0 6.0 2.9 6.0 Adhesion fastness No shedding No shedding No shedding Severe shedding Severe shedding No shedding No shedding No shedding Average square resistance of A surface (Ω / sq) 1052 2820 123 - - 2192 1871 729 Variation coefficient of square resistance of A surface (%) 5.9 4.5 6.1 - - 7.3 7.5 6.2 Average square resistance of B side (Ω / sq) 1029 2954 108 - - 2086 1794 682 Coefficient of variation of B-side square resistance (%) 4.2 5.6 5.8 - - 7.9 6.5 5.9 Heating temperature (120℃) Stablize Stablize Stablize - - Stablize Stablize Stablize Repeated heating resistance change rate (%) 1.8% 2.8% 1.2% - - 25.6% 21.3% 18.5% Tensile strength (MPa) 182 35.8 252.1 - - 135 115 153 Elastic modulus (MPa) 1906 78.4 2966 - - 1164 849 1093
[0070] As can be seen from Table 1:
[0071] (1) The results of Examples 1-3 show that the conductive glass fiber cloth of the present invention has the characteristics of uniform and stable square resistance, good coating adhesion, and excellent impact resistance. It can be heated to 120°C and has high stability in repeated heating.
[0072] (2) The results of Example 1 and Comparative Examples 1 and 2 show that when the conductive ink without low-melting-point glass powder is used, the conductive layer falls off over a large area due to carbonization, resulting in black powder on the surface and no adhesion. This indicates that the low-melting-point glass powder acts as a protective layer and connects the conductive component and the glass fiber cloth during calcination.
[0073] (3) The results of Example 1 and Comparative Example 3 show that, before calcination, the conductive layer has good adhesion, but its square resistance is relatively large. After calcination, the square resistance is significantly reduced. Furthermore, the uncalcined conductive glass fiber cloth exhibits a large resistance change rate after repeated heating, which may be due to structural changes in the conductive network during intermittent heating.
[0074] (4) The results of Comparative Examples 3, 4, and 5 show that, when the conductive ink is used without the addition of low-melting-point glass frit, the dry weight of the conductive layer decreases, but its sheet resistance slightly increases. Further increasing the dry weight increases the thickness of the conductive layer and further decreases its sheet resistance. This is likely due to the denser structure of the conductive layer, indicating that the low-melting-point glass frit exists only as a filler in the conductive layer before calcination.
[0075] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A conductive glass fiber cloth, characterized in that: The invention comprises a glass fiber base cloth and a carbonized conductive layer formed on the glass fiber base cloth; the carbonized conductive layer is obtained by coating a conductive ink and calcining the carbonized conductive layer; the components of the conductive ink are composed of the following components in parts by weight: 10-30 parts of low-melting-point glass powder, 3-5 parts of graphene, 0.5-2 parts of single-walled carbon nanotubes, 0.1-0.5 parts of conductive carbon black, 5-10 parts of resin, 0.1-0.3 parts of dispersant, 0.01-0.03 parts of anti-settling thixotropic agent, 0.01-0.05 parts of silane coupling agent, 70-90 parts of water and 5-20 parts of ethanol.
2. The conductive glass fiber cloth according to claim 1, characterized in that: The specification of the low melting point glass powder is 1500 mesh-3000 mesh.
3. The conductive glass fiber cloth according to claim 1, characterized in that: The sheet diameter of the graphene is ≤6 μm, and the number of layers is 6-10; the diameter of the single-walled carbon nanotube is 1-2 nm, and the length is 10-30 μm; and the mesh number of the conductive carbon black is 1000-2000 mesh.
4. The conductive glass fiber cloth according to claim 1, characterized in that: The resin is at least one of polyurethane resin and ceramic resin; the dispersant is polyvinyl pyrrolidone K30; the anti-settling thixotropic agent is one of polyamide wax and polyethylene wax; the silane coupling agent is one of vinyl silane, amino silane and methacryloxy silane.
5. The conductive glass fiber cloth according to claim 1, characterized in that: Low melting point glass powder, graphene, single-walled carbon nanotubes, conductive carbon black, resin, dispersant, anti-settling thixotropic agent and silane coupling agent are uniformly mixed in a mixed solvent consisting of water and ethanol to obtain conductive ink.
6. The conductive glass fiber cloth according to claim 1, characterized in that: The conductive ink is coated on the glass fiber cloth by spraying or dipping.
7. The conductive glass fiber cloth according to claim 1 or 6, characterized in that: The coating dry weight of the conductive ink is 2-30 g / m 2 .
8. The conductive glass fiber cloth according to claim 1, characterized in that: The calcination is carried out in an inert atmosphere, using a gradient temperature rise calcination method, the steps are: firstly heating to a drainage temperature of 130-150°C, and keeping the temperature for 5-10 minutes; Then raise the temperature to the carbon removal temperature of 350-380℃ and keep it warm for 5-10 minutes; continue to raise the temperature to the sintering temperature of 400-600℃ and keep it warm for 10-30 minutes.
9. The conductive glass fiber cloth according to claim 8, characterized in that: The inert atmosphere is at least one of nitrogen, helium and argon.
Citation Information
Cited By
Conductive heating graphene glass fiber cloth and preparation method thereof
CN120989903A
An electrically conductive and heatable graphene glass fiber cloth and a method for preparing the same
CN120989903B